Citelli abscess: A rare case - Yuanzhi, Cheah; Boon Han, Kevin Ng; Moses, Shamina Sara; Tang, Ing Ping (Malaysian Medical Association, 2021)
Citelli abscess is a complication of otitis media which is rarely encountered nowadays due to the availability of antibiotics. Clinical features include mastoid and occipital swelling, pain and fever. High resolution computed tomography (HRCT) scan of the temporal region can aid in the diagnosis. Early surgical intervention can improve the outcome. A 11-year-old girl presented with a 1month history of painful right post auricular swelling without any other otological symptoms. On examination, a huge, erythematous and tender swelling involving the post auricular and occipital region was noted. The otological examination was unremarkable. HRCT scan showed right occipital collection with fluid in the mastoid air cells and mastoid wall erosion. The patient underwent a mastoid exploration and right cortical mastoidectomy which revealed copious pus and necrotic tissue at the soft tissue layer overlying the mastoid bone with associated erosion of the mastoid air cells and the bony covering of the transverse and sigmoid sinus. Post operatively, the patient recovered uneventfully after completing 5 days of intravenous antibiotics. At the outpatient clinic visit one month after surgery, the patient was well. Citelli’s abscess is rare and may present without any otological clinical features. A high index of clinical suspicion with radiological assessment are essential in arriving at the diagnosis. Early surgical intervention produces good outcomes.